Vietnamese secondary school EFL students’ motivation and attitudes toward using ChatGPT for vocabulary learning - Thuan Anh Pham; Cuong Huy Pham (Institute of Advanced Engineering and Science, 2026)
The escalating adoption of artificial intelligence (AI) in language education, particularly ChatGPT, has drastically altered vocabulary teaching and learning practices in secondary schools in Vietnam, where rote learning and teacher-centered approaches are common norms. This study examines secondary school students’ motivation and attitudes toward using ChatGPT for vocabulary development. A mixed-methods design was employed, drawing on a survey with 208 ninth-grade students and semi-structured interviews with eight of the respondents. The survey data revealed the students’ moderate degrees of motivation to use ChatGPT, with extrinsic motivation surpassing intrinsic motivation. Their attitudes were generally positive, showing relatively high enjoyment and low anxiety in utilizing ChatGPT for vocabulary learning. The students considered ChatGPT a useful and convenient resource and expressed willingness to continue using it despite their concerns over its reliability and the risk of over-reliance. The interview data augmented these patterns, highlighting ChatGPT’s interactivity and flexibility while emphasizing the continued importance of teachers’ classroom support. This study provides corroborating evidence for ChatGPT as a versatile complementary tool for vocabulary learning that fosters learners’ motivation and positive attitudes. However, its adoption requires careful integration with teacher guidance and AI literacy training.